(untitled) - Hayter, Anthony J (Belmont, Calif., 2007)
The new edition of Anthony Hayter's book continues in the same student-oriented vein that has made previous editions successful. Because Tony Hayter teaches and conducts research at a premier engineering school, he is in touch with engineers daily and understands their vocabulary. This leads to a clear and more readable writing style that students understand and appreciate. Additionally, because of his intimacy with the professional community, Hayter includes many high-interest examples and datasets that keep students' attention throughout the term
Keywords: Engineering,Probabilities,Toán thống kê; Statistical methods